2012
DOI: 10.5334/snr.ad
|View full text |Cite
|
Sign up to set email alerts
|

Forms, Frequency, and Correlates of Perceived Anti-Atheist Discrimination

Abstract: The nationally representative 2008 American Religious Identification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
121
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(124 citation statements)
references
References 98 publications
2
121
1
Order By: Relevance
“…Thus, it is important to investigate the ways that people who exist at the intersections of transgender and nonreligious identity experience, make sense of, and participate the cissexist and highly religious world around them. The insights from the present literature on both nonreligious and transgender experience show that the U.S. is a society dominated by religious norms (Barton 2012;Hammer et al 2012), and that nonreligious people (both those affiliated with nonreligious groups and not) work against this marginalization through various identity construction tactics (Cimino and Smith 2007;. Since religious institutions (Stack 2015;) -and religious (Urquhart 2015) and nonreligious leaders (Walker 2015) -have started to reproduce cissexism in their discussions of transgender people, it may be time for scholars of nonreligion to pay close attention to the ways that transgender existence intersects with nonreligious identity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, it is important to investigate the ways that people who exist at the intersections of transgender and nonreligious identity experience, make sense of, and participate the cissexist and highly religious world around them. The insights from the present literature on both nonreligious and transgender experience show that the U.S. is a society dominated by religious norms (Barton 2012;Hammer et al 2012), and that nonreligious people (both those affiliated with nonreligious groups and not) work against this marginalization through various identity construction tactics (Cimino and Smith 2007;. Since religious institutions (Stack 2015;) -and religious (Urquhart 2015) and nonreligious leaders (Walker 2015) -have started to reproduce cissexism in their discussions of transgender people, it may be time for scholars of nonreligion to pay close attention to the ways that transgender existence intersects with nonreligious identity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Discrimination against atheists manifests in many overt ways as well, including slander and ostracism (HAMMER, CRAGUN, SMITH, 2012). In at least 13 countries, atheists, apostates, or blasphemers face legal consequences as severe as the death penalty (IHEU, 2014).…”
Section: Interpersonal Strugglementioning
confidence: 99%
“…A number of studies have considered the extent to which non-religious adults experience discrimination in the US, despite a lack of systematic research in this area. Cragun et al (2012) found that 22% of their sample reported some form of discrimination, most frequently in social or family contexts, whereas at least 75% of participants in the Hammer et al (2012) study had experienced a range of different types of discrimination, including witnessing antiatheist comments in the media, being expected to participate in religious prayers against one's will and being told one's atheism is sinful, wrong or immoral. The literature also includes many anecdotal illustrations of discrimination, including job dismissals, death threats, physical violence, family rejection, and denial of employment, service and membership of community organisations .…”
Section: Youth Citizenship and Social Cohesionmentioning
confidence: 99%